Menjaga Privasi Digital: Studi Tentang Kesadaran Mahasiswa dalam Perlindungan Data Pribadi di Media Sosial - Nopriadi Nopriadi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Many people utilize social media to interact, including students who are the most technologically literate. Apart from having a positive impact on its users, social media also has a negative impact. One of the negative impacts of social media is the increased risk of personal data security. The purpose of this study is to analyze the level of awareness of students in Yogyakarta regarding the protection of personal data on social media. The method used is mixed method, surveys were distributed to respondents, namely students from various schools in Yogyakarta. Researchers also conducted interviews with 15 participants to get a more in-depth picture. This research examines the level of understanding and awareness of students in Yogyakarta regarding how they understand data sharing behavior, privacy settings and their perceptions of threats or risks in cyberspace. The results showed that the majority of students have a high level of awareness regarding basic privacy measures, but they also have a poor understanding of the threats and risks associated with sharing personal data.The majority of students rarely update their privacy settings. They only use the default settings built into social media. The implication of the study is the need to integrate digital literacy programs that focus on data security and privacy into the school curriculum. The conclusion is that there is awareness among students regarding the importance of protecting personal data, but more efforts are needed to improve students' knowledge in digital privacy management. Further research is needed to assess the long-term impact of educational interventions on privacy-conscious behavior in the digital world.